Bibliometric analysis of Malaysian Orthopaedic Journal using Scopus database - Kow, Ren Yi; Low, Chooi Leng; Zulkifly, Ahmad Hafiz (Malaysian Orthopaedic Association (MOA) and ASEAN Orthopaedic Association (AOA), 2024)
(ISSN 1985-2533 / 2232-111X) is the official publication of the Malaysian Orthopaedic Association (MOA) and the ASEAN Orthopaedic Association (AOA). In May 2007, MOA published the first standalone issue of MOJ with the aim of disseminating new knowledge and providing updates in orthopaedics, trauma and musculoskeletal research. Since then, MOJ has grown significantly, achieving indexing in numerous databases and attaining a 2nd Quartile (Q2) rank in the Scopus database in 2022. This bibliometric analysis aims to explore the trends and distribution of articles published in MOJ. Materials and methods: Bibliometric data for MOJ was extracted from the SCOPUS database, covering the years from its indexing to 2022. Information such as authors, country, document type, author’s keywords, citations, and other parameters were extracted using the bibliometrix package in the R Studio software. The data were then presented in tables and illustrative graphs using the same software. Results: A total of 305 articles were retrieved from the Scopus database during the study period. Two-thirds of the articles were original articles and review articles. The highest number of citations received by an article is 56, and top ten articles in MOJ were authored by researchers from seven different countries, highlighting the journal’s diversity. Despite receiving submissions from various countries, there is minimal collaboration between authors of different countries. Keywords such as “covid-19” and “pandemic” dominate the authors’ keyword section due to the once-in-a-life-time COVID-19 which during the study period, resulting in numerous publications related to this issue. Conclusion: This bibliometric analysis reviews all the articles indexed in the Scopus database and provides insight into the contributors’ information and the trends in orthopaedic research. By identifying the lack of collaboration between countries, it is hoped that this analysis can inspire more orthopaedic surgeons and researchers to collaborate and produce high-quality publications.